Nanotechnology showdown: Chitosan-proline nanoparticles improve Mentha spicata L. tolerance against CuO nanoparticle toxicity - Milani, Maryam Haghmadad; Panahirad, Sima; Kulak, Muhittin; Zhou, Jie; Gohari, Gholamreza; Fotopoulos, Vasileios (My University, 2025)
Excessive accumulation of copper oxide nanoparticles (CuO NPs) in agricultural soils poses significant risks to plant growth, physiology, and secondary metabolism due to induced oxidative stress and metal toxicity. The present study hypothesized that foliar application of chitosan-proline nanocomposites (Pro-CTS NPs) could mitigate CuO NP-induced phytotoxicity in spearmint (Mentha spicata L.) by enhancing physiological resilience and defense mechanisms including enzymatic and non-enzymatic antioxidants. As expected, increasing CuO NP concentrations (100 and 200 mg kg-1 soil) caused significant reductions in biomass- and photosynthesis-linked traits, along with elevated levels of malondialdehyde (MDA), hydrogen peroxide (H₂O₂), and Cu accumulation. Remarkably, foliar treatments with Pro-CTS NPs (25 and 50 mg L-1) significantly improved plant growth, restored chlorophyll and carotenoid levels, enhanced EO yield, and reduced Cu uptake. The observed effects were clearly aligned with induced activities of antioxidant enzymes (superoxide dismutase, ascorbate peroxidase, guaiacol peroxidase), as well as higher proline and phenolic contents. Such changes were translated into significantly alleviated cellular oxidative damage. Regarding biosynthesis of metabolites, Pro-CTS NPs may optimize or redirect metabolic fluxes toward desirable secondary metabolites. Overall, current findings demonstrate that, under the tested conditions, Pro-CTS NPs acted as an effective nanobiotechnological priming strategy for spearmint exposed to CuO NP stress, providing dual protective and biostimulatory effects. Further studies are required to determine whether these benefits extend to other plant species, stress types, and field environments.
Keywords: Nanotechnology; Abiotic stress; Antioxidants enzymes; Heavy metals; Medicinal Plants